The effect of resonant magnetic perturbation on the electron density threshold of runaway electron generation during disruptions on J-TEXT. (20th December 2019) - Lin, Z F; Tong, R H; Chen, Z Y; Huang, D W; Li, C H; Wei, Y N; Li, D; Zhou, S; Hu, J; Li, W; Huang, Y; Yang, H Y; et al.
Abstract: The generation of runaway electrons (REs) during disruptions is a key issue for the safe operation of large tokamaks. For better design, a reliable scenario to suppress RE generation and for the investigation of RE generation during disruptions is highly essential. On J-TEXT, RE generation is strongly dependent on the pre-disruption electron density, toroidal magnetic fields ( B T ) and magnetic perturbations. RE generation can be avoided in discharges with a low B T or a high electron density. For discharges with a high B T, a high electron density threshold is required to suppress RE generation. However, this threshold decreases with the application of resonant magnetic perturbations (RMP) which is applied before the thermal quench. The enhancement of magnetic perturbation increases the RE loss during disruptions, leading to robust runaway suppression in the discharges with a relatively low electron density. The electron density threshold required for RE suppression reduces with the increase of RMP strength and the m / n  = 2/1 mode RMP is more efficient than the m / n  = 3/1 mode RMP for the reduction of density threshold, where m and n are the poloidal and toroidal mode numbers, respectively. The NIMROD simulation is applied to investigate the transport of REs during disruptions, which indicates that the 2/1 mode RMP can create stronger magnetic perturbations during a disruption, resulting in a high loss ratio of RE seeds. All results provide evidence of the significant effect of RMP mode and amplitude on the electron density threshold for RE generation, which might give an insight into future large reactor tokamak operation with high electron densities.